Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1017/s0950268816001035
|View full text |Cite
|
Sign up to set email alerts
|

Quantified degree of poultry exposure differs for human cases of avian influenza H5N1 and H7N9

Abstract: Preliminary evidence suggests that direct poultry contact may play a lesser role in transmission of avian influenza A(H7N9) than A(H5N1) to humans. To better understand differences in risk factors, we quantified the degree of poultry contact reported by H5N1 and H7N9 World Health Organization-confirmed cases. We used publicly available data to classify cases by their degree of poultry contact, including direct and indirect. To account for potential data limitations, we used two methods: (1) case population met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…In 2013 a new subtype H7N9 emerged in humans in China and the human case count by December 2016 was over 795, with over 314 deaths [2]. Differences in the epidemiology of H7N9 and H5N1 have previously been described: human H5N1 cases report higher severity of disease [3] and higher levels of contact with sick or dead birds [4]; H7N9 is asymptomatic in birds [5] and found at lower prevalence rates in poultry [6]; and the spatial distribution of H5N1 within a comparable time frame is considerably greater than that of H7N9 [3]. This study aimed to improve upon our current understanding of the spreading mechanisms behind H7N9 and H5N1, provide a geographic risk profile for each of the two virus subtypes across all of mainland China, and highlight the regions at greatest risk of experiencing AIV transmission.Implementing effective AIV control measures in China to prevent spread among domestic poultry population, and transmission to humans, is a recognized challenge.…”
mentioning
confidence: 99%
“…In 2013 a new subtype H7N9 emerged in humans in China and the human case count by December 2016 was over 795, with over 314 deaths [2]. Differences in the epidemiology of H7N9 and H5N1 have previously been described: human H5N1 cases report higher severity of disease [3] and higher levels of contact with sick or dead birds [4]; H7N9 is asymptomatic in birds [5] and found at lower prevalence rates in poultry [6]; and the spatial distribution of H5N1 within a comparable time frame is considerably greater than that of H7N9 [3]. This study aimed to improve upon our current understanding of the spreading mechanisms behind H7N9 and H5N1, provide a geographic risk profile for each of the two virus subtypes across all of mainland China, and highlight the regions at greatest risk of experiencing AIV transmission.Implementing effective AIV control measures in China to prevent spread among domestic poultry population, and transmission to humans, is a recognized challenge.…”
mentioning
confidence: 99%
“…Human cases of AIV infection have typically in the past been exposed to virus via infected poultry on farms or markets, however in recent years, and particularly in China, occurrence of human infection have largely been in association with visiting live bird markets (LBMs) rather than close contact with poultry [7]. However, exposure details are missing for a large proportion of cases (see Additional file 1: Table S1 and [3, 7]).…”
Section: Resultsmentioning
confidence: 99%
“…However, exposure details are missing for a large proportion of cases (see Additional file 1: Table S1 and [3, 7]). We have shown that a history of close poultry contact is far more common for human H5N1 cases than H7N9 cases [7]. In the latter case, a history of incidental poultry contact (such as walking through LBMs) is more common [7].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 The leading cause of death in infected patients is diffuse alveolar damage and hemorrhage in the lungs, which is caused by overactive inflammatory responses. 12,13 Overproduction of inflammatory cytokines in H5N1-infected mice and humans, referred to as a cytokine storm, has been identified as the main cause of death associated with this virus. 14,15 Vaccination remains the most effective preventive measure against influenza viruses.…”
Section: Introductionmentioning
confidence: 99%